Advanced penetration testing for highly-secured environments : the ultimate security guide : learn to perform professional penetration testing for highly-secured environments with this intensive hands-on guide - Allen, Lee (Information security specialist) (Packt Pub., 2012)
Learn to perform professional penetration testing for highly-secured environments with this intensive hands-on guide with this book and ebook.
Keywords: Computer security -- Testing -- Handbooks, manuals, etc.; Penetration testing (Computer security) -- Handbooks, manuals, etc.; Computer networks -- Security measures -- Handbooks, manuals, etc.; Computer networks -- Handbooks, manuals, etc.; elektronické knihy; electronic books